2021
DOI: 10.3390/ma14071619
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Highly Porous Replicated Aluminum Foam Using Double-Granular Space Holder

Abstract: Porous materials are widely employed in a wide variety of industrial applications due to their advanced functional performance. Porous aluminum is among the most attractive metallic materials. It can be produced using repeatable methods involving a replicated Al foam that also provides porosity control. In this work, a highly porous replicated Al foam was fabricated. First, the model of multifunctional packing density was used and corrected to select the appropriate space holders. Then, Al foam was produced us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Ozer et al [13] described, in their paper, a method of producing open-cell aluminum foams, for which they used as the space holder furan bonded sand and gypsum bonded ceramics, whereas the metal matrix was aluminum alloy A413. Finkelstein et al [14] showed the production methodology of highly porous replicated aluminum foam using a double-granular space holder. Sutygina et al [15] have presented the manufacturing of open-cell copper foam using the sponge replication technique.…”
Section: Introductionmentioning
confidence: 99%
“…Ozer et al [13] described, in their paper, a method of producing open-cell aluminum foams, for which they used as the space holder furan bonded sand and gypsum bonded ceramics, whereas the metal matrix was aluminum alloy A413. Finkelstein et al [14] showed the production methodology of highly porous replicated aluminum foam using a double-granular space holder. Sutygina et al [15] have presented the manufacturing of open-cell copper foam using the sponge replication technique.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the advantage also serves as a great drawback to the manufacturability of aluminum products, which thus leads to a great hurdle for manufacturing industries to fully cultivate the potential and usage of pure aluminum in manufacturing industries [4]. In recent years, various approaches have been explored in the manufacturing of porous aluminum with different fabrication methods and reinforcement materials which opens many possibilities for the manufacturing, construction, automotive, and building industries [5][6][7]. For instance, open-celled porous aluminum had been depicting great functionality in sound damping elements, heat exchanger elements, filters, and design elements, which are particularly adopted in the building and construction industry [5].…”
Section: Introductionmentioning
confidence: 99%